OPENNESS AND GROWTH: STILL AN OPEN QUESTION?1. (November 2013) - Winters, L. Alan; Masters, Andrew; Lawson, David; Amann, Edmund
Abstract We review recent empirical literature on the relationship between openness and the level of national income or, nearly equivalently, trade liberalisation and economic growth. Recent advances reinforce the presumption of a positive causal link from trade to income, especially by solving endogeneity issues more carefully than heretofore and by allowing for heterogeneity between countries. Heterogeneity suggests that low‐income countries may benefit less from trade liberalisation than do other countries, but this is not completely settled. We also argue for analysing policy decisions on trade policy with tools from decision theory rather than those from hypothesis testing. © 2013 Crown copyright. Journal of International Development © 2013 John Wiley & Sons Ltd.